IMPROVING STUDENTS’ ACHIEVEMENT IN READING COMPREHENSION THROUGH PREVIEW,QUESTION, READ,REFLECT, RECITE, AND REVIEW (PQ4R) - Mediana Manalu and Bachtiar (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2014)
This study concerned on improving students’ achievement in readaing comprehensionnarrative text through preview, question, read, reflect, recite, and review (PQ4R) technique.This study was limited on the second year junior high school students’ achievement inreading comprehension after teaching by applying preview,question, read, reflect, recite, andreview ( PQ4R).The objective of this study was to find out the improvement of students,achievement on reading comprehension through PQ4R technique.The subject of the studywas VIII-1 students of SMP N 4 Pagaran. The numbers of the students were 35. Thetechniques for data analysis were quantitative dataand qualitative data.In analyzing thequantitative data, the mean of the students’ score for the test I cycle I was 53.62, the meanscore of test II in cycle II was 73.28, the mean of test III in cycle II was 75.65. Theconclusion is that PQ4R can improve the students’ achievement in reading comprehensionnarrative text.